Preserving Swarm Identity Over Time - James Stovold (ALIFE 14: The Fourteenth Conference on the Synthesis and Simulation of Living Systems, 2014)
Collective identity helps swarms remain coherent in the presence of others. Building identity into artificial systems enables groups of agents to work in the same area as one another, without interference from other agents. By linking the firefly algorithm to the control logic of the agents, we present a method to form and maintain identity in swarms. By measuring swarm polarization, and swarm overlap, we show that the inclusion of an identity allows a swarm to remain coherent for an extended period of time, without interference from other swarms.